2010
DOI: 10.1007/s00442-010-1693-2
|View full text |Cite
|
Sign up to set email alerts
|

Increased relative abundance of an invasive competitor for pollination, Lythrum salicaria, reduces seed number in Mimulus ringens

Abstract: When exotic plant species share pollinators with native species, competition for pollination may lower the reproductive success of natives by reducing the frequency and/or quality of visits they receive. Exotic species often become numerically dominant in plant communities, and the relative abundance of these potential competitors for pollination may be an important determinant of their effects on the pollination and reproductive success of co-occurring native species. Our study experimentally tests whether th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(37 citation statements)
references
References 64 publications
0
35
1
Order By: Relevance
“…Like other studies of competition for pollination between L. siphilitica and M. ringens (e.g., Bell et al 2005;Flanagan et al 2010Flanagan et al , 2011, we used an additive design. An additive design has both advantages and disadvantages (reviewed in Inouye 2001).…”
Section: Experimental Designmentioning
confidence: 99%
“…Like other studies of competition for pollination between L. siphilitica and M. ringens (e.g., Bell et al 2005;Flanagan et al 2010Flanagan et al , 2011, we used an additive design. An additive design has both advantages and disadvantages (reviewed in Inouye 2001).…”
Section: Experimental Designmentioning
confidence: 99%
“…Invasion by exotic plant species can alter floral neighborhoods by changing floral density and diversity (Lázaro and Totland 2010b). These neighborhood characteristics are known to influence pollinator foraging behavior (Muñoz and Cavieres 1996, Kunin 1997, Bosch and Waser 2001, Ghazoul 2006, Bartomeus et al 2008, Flanagan et al 2010, Yang et al 2011). Furthermore, foraging behavior in a given floral neighborhood can be contingent on pollinator identity, as pollinator groups may behave differently in the same floral environment (Stout et al 1998, Lázaro and Totland 2010a, b).…”
mentioning
confidence: 99%
“…Although we found little evidence of competition between C. stoebe and H. villosa for pollinators at low relative densities of C. stoebe, we observed a trend (non-significant) of decreasing visits per flower to H. villosa with increasing density of C. stoebe, indicating that there may be competition at greater densities of C. stoebe than we tested. Other studies investigating the impact of the relative abundance of an invasive plant on pollinator visitation to a coflowering native plant have found mixed results, including facilitative, competitive and neutral interactions (Muñoz and Cavieres 2008, Flanagan et al 2010, Chung et al 2014. A meta-analysis of seven studies found an increasing negative impact on visitation to and reproduction of native plants with increasing abundance of the invasive plant (Morales and Traveset 2009).…”
Section: Discussionmentioning
confidence: 97%
“…Other studies investigating the impact of the relative abundance of an invasive plant on pollinator visitation to a co‐flowering native plant have found mixed results, including facilitative, competitive and neutral interactions (Muñoz and Cavieres , Flanagan et al. , Chung et al. ).…”
Section: Discussionmentioning
confidence: 99%